Inheritance and Molecular Mapping of an All-Stage Stripe Rust Resistance Gene Derived from the Chinese Common Wheat Landrace "Yilongtuomai". (19th May 2016) - Wu, Xue-Lian; Wang, Jian-Wei; Cheng, Yu-Kun; Ye, Xue-Ling; Li, Wei; Pu, Zhi-En; Jiang, Qian-Tao; Wei, Yu-Ming; Deng, Mei; Zheng, You-Liang; Chen, Guo-Yue
Abstract : Yellow or stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is a devastating foliar disease that affects common wheat ( Triticum aestivum L.) around the world. In China, common wheat landraces are potential sources of disease and abiotic stress resistance genes for wheat improvement. Yilongtuomai (YL), a wheat landrace from Yilong County, Sichuan Province, shows high levels of resistance against most Chinese Pst races. In this study, the resistance of YL to stripe rust disease was examined in detail. Parent strains, YL and Taichung 29, a variety susceptible to Pst race CYR32, and their F1, F2, and F2:3 offspring, were inoculated with CYR32 during the seedling stage in the field or adult-plant stage in the greenhouse. Results indicated that resistance to CYR32 in YL is conferred by a single dominant gene, designated YrYL . The segregating F2 population (352 plants), was analyzed in terms of its resistance locus using simple sequence repeats (SSRs), resistance gene analog polymorphisms (RGAPs), and sequence-related amplified polymorphism (SRAP). A linkage group of 6 SSRs, 2 RGAPs, and 1 SRAP was constructed for the YrYL gene. Using the identified SSRs associated with physical mapping of RGAP using Chinese Spring nullisomic–tetrasomic stocks, the YrYL gene was localized to the short arm of chromosome 7D. The gene was flanked by 1 SSR marker, Xbarc92, and 1 RGAP marker, CLRRfor/Ptokin4, at genetic distances of 5.35 and 9.86 cM, respectively. The YrYL gene was compared to other stripe rust resistance genes reported on chromosome 7D by evaluating its reaction patterns to CYR32 and its pedigree relationship. Our results suggest that the YrYL gene is a new stripe rust resistance gene.